The Making of the ’Burgundian Kingdom’ - Wood, Ian (Reti Medievali Rivista, 2021)
What is usually called the Burgundian kingdom differed in various respects from the other ’successor states’ of the fifth and sixth centuries. It was not a territorial entity associated with a people, but was rather a region of the later Roman Empire that was controlled by members of the Gibichung family who were put in post by the imperial administration in Italy, especially by Ricimer, to whom they were connected by marriage. Their advisers, who included Sidonius Apollinaris, were Romans. And they continued to act as imperial agents down to the 520s.